Entrepreneurial Management in Realizing Student Entrepreneurship Education at SMKN 1 Buduran Sidoarjo - Oktavianasari, Dinna; Khamidi, Amrozi; Sholeh, Muhamad; Purwoko, Budi (Journal of English Language and Education, 2025)
This study aims to analyze and evaluate entrepreneurial management—covering Planning, Organizing, Implementing, and Supervising (POAC)—in realizing entrepreneurship education at SMKN 1 Buduran Sidoarjo. The research problem focuses on how the school’s Teaching Factory, particularly the Titik Satu Kopi school café, manages its entrepreneurial program to develop students’ entrepreneurial character amid the challenges of the Industrial Revolution 5.0 and the high unemployment rate among vocational graduates. This study employs a qualitative descriptive approach using a case study design. Data were collected through in-depth interviews with the principal, vice principal for curriculum, café manager, and supervising teachers; direct observation of café operations and student practice activities; and document analysis related to school entrepreneurship programs. Data were analyzed using the Miles and Huberman model—data reduction, data display, and conclusion drawing. The findings indicate three main results: (1) entrepreneurial management at SMKN 1 Buduran is effectively implemented through structured POAC stages, supported by BLUD regulations that provide financial and managerial flexibility; (2) the Teaching Factory café strengthens students’ entrepreneurial character, particularly proactivity, innovation, responsibility, and risk-taking skills through real business practice; and (3) the café functions not only as a business unit but also as a practical learning laboratory that aligns school programs with industry standards. Theoretically, the study provides a model integrating managerial functions with practical entrepreneurship learning in vocational education. Practically, the findings offer recommendations for strengthening Teaching Factory management and serve as a reference for other vocational schools seeking to implement entrepreneurship-based learning.